PIRLS XALÍQARALÍQ BAǴDARLAMA TALAPLARÍ TIYKARÍNDA BASLAWÍSH KLASS OQÍWSHÍLARÍNÍŃ KOMMUNIKATIVLIK KOMPETENCIYALARÍN QÁLIPLESTIRIW - Utemuratov, B.K. (SCIENCE and SOCIETY, 2023)
The article provides recommendations on the methods of formation of communicative competencies of primary school students in secondary schools based on the requirements of the international PIRLS study, the tasks of orientation of students to logical thinking in the classroom.